CREATING INTERACTIVE COMPETENCE IN PROFESSIONALLY-ORIENTED FOREIGN LANGUAGE (ON THE EXAMPLE OF STUDENTS OF SPECIALTY «FINE ARTS AND DRAWING») - Тleuzhanova, G.K.; Тleuzhanova, K.Т.; Ayazbayeva, S.S. (Халықаралық ғылыми форум МАТЕРИАЛДАРЫ 6–8 сəуір, 2016)
This article deals with the problems of formation of the interactive competence at training professionally oriented foreign language. The authors suggested brief recommendations for the use in the educational process of training manuals which are aimed at job creation interactive competence of students. Also there is practical achievement of the research which is determined in the textbook.
Keywords: interactive competence; speech skills; communication; expert; professional communication; интерактивная компетенция; навыки говорения; коммуникация; эксперт; профессиональное общение